Molecular docking based virtual screening of carbonic anhydrase IX with coumarin (a cinnamon compound) derived ligands - Meenakumari, Krishnamoorthy (Bioinformation, 2019)
It is of interest to design carbonic anhydrase IX (CAIX) inhibitors with improved features using molecular docking based virtual high through put screening of ligands. Coumarin (a cinnamon compound with pharmacological activity) is known as a potent phytal compound blocking tumor growth. Hence, a series of 17 coumarin derivatives were designed using the CHEMSKETCH software for docking analysis with CAIX. The catalytic site analysis of CAIX for binding with ligand molecules was completed using the SCHRODINGER package (2009). Thus, 17 ligands with optimal binding features with CAIX were selected following the calculation of ADME/T properties. We report ligands #41, #42, #19 and #15 showed good docking score, glide energy and hydrogen bond interactions without vdW clash. We further show that N-(3,4,5-trimethoxy-phenylcarbamoylmethyl) designated as compound #41 have the highest binding energy (-61.58) with optimal interactions with the catalytic residues (THR 199, PRO 201, HIS 119, HIS 94) of CAIX.